Plastic Shaman in the Global Village:: Understanding Media in Thomas King’s Green Grass, Running Water - Johnson, Brian (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2000)
"The book" — meaning the written word, from the Bible to European literature to the colonisers' documented histories of the Native other — has been one of the principal sites of colonial aggression. The oral tradition of the North American Native has been a crucial signpost of their perceived inferiority; but in Thomas King's Green Grass, Running Water, it is also a method of resistance to the epistemic — as well as the material — violence of the colonial encounter. Yet this is not a simple binary opposition, as King strives to complement what he has termed a Native "interfusional literature," a hybrid of heretofore oppositional traditions. The effects of other forms of Western technology and media are similarly examined both in terms of their intrinsic "imperialist biases" and their innate propensities for resistance and hybridity.